Perancangan Interior Gedung Bioskop Cinemaxx Berbasis Greenship di Surabaya - Goey Fenny; Hedy Constancia Indrani; Purnama Esa Dora (Intra, 2018)
Cinema is one of the favorite entertainment place, especially for movie lovers, children and adults. It is often located in a shopping mall with similar design concept because of using the same brand of cinema. Frequently, the cinema design does not give much attention to the energy efficiency aspect. The design method consists of literature studies; design typology; online interview with Surabaya townspeople; observe location and prospect users; analyze data; state the problem; present the idea in shop drawing and presentation drawing. The design goal is to create a healthy and eco-friendly cinema by applying various variables of Greenship Interior Space Version 1.0. The other purpose is to create a different cinema’s environment in Surabaya which able to support user’s complex activities with various facilities. The cinema design uses a new building and branding in Surabaya. Cinemaxx cinema is designed to create a new and exciting atmosphere for Surabaya townspeople when enjoying the movie and receive gold certification level from Greenship Interior Space Version 1.0.